Italian forgers : the art market and the weight of the past in modern Italy - Helstosky, Carol (Cornell University Press, 2024)
"Italian Forgers takes an unorthodox approach to a popular topic: art forgery. Based on original published sources as well as current and past scholarship, Italian Forgers focuses not on art forgery per se, but on the major forgery scandals in the context of a shifting art market operated by a number of Italians who fashioned a very sophisticated and self-conscious response to the constant and often intense demand for Italian objects."--